Evaluation of Cyclooxygenase-2 and p53 Expression in Pterygium Tissue Following Preoperative Intralesional Ranibizumab Injection - Omar, Ahmad Razif; Ibrahim, Mohtar; Jaafar, Hasnan; Siti-Azrin, Ab Hamid; Zunaina, Embong (Frontiers in Medicine, 2021)
Introduction: Overexpression of vascular endothelial growth factor (VEGF), cyclooxygenase-2 (COX-2) and p53 are the postulated aetiopathogenesis in pterygium. VEGF is responsible for the induction of COX-2 expression, whereas p53 plays an important role in the regulation of VEGF. The aim of this study was to evaluate the immunohistochemistry of COX-2 and p53 expression from excised pterygium tissue from patients who received intralesional ranibizumab (anti-VEGF) injection two weeks prior to pterygium surgery. Materials and Methods: An interventional comparative study involving patients presenting with primary pterygium was conducted between September 2015 and November 2017. The patients were randomized into either the intervention or control group. Patients in the intervention group were injected with intralesional ranibizumab (0.5 mg/0.05 mL) two weeks prior to surgery. Both groups underwent pterygium excision followed by conjunctival autograft. Immunohistochemistry staining was performed to evaluate COX-2 and p53 expression in the excised pterygium tissue. Results: A total of 50 patients (25 in both the intervention and control groups) were recruited. There were 34 (68%) patients with grade III pterygium and 16 (32%) patients with grade IV pterygium. There was statistically significant difference in reduction of COX-2 expression in the epithelial layer [84.0% (63.9,95.5)] (p=0.007) and stromal layer [84.0% (63.9,95.5)] (p<0.001) between intervention and control groups. There was no significant difference in the reduction of p53 expression between the two groups. Conclusion: This study demonstrated the possible use of intralesional anti-VEGF treatment prior to pterygium excision as a potential future modality of adjunctive therapy for pterygium surgery.